Geriatric Cardiology: An Emerging Discipline - Dodson, John A.; Matlock, Daniel D.; Forman, Daniel E. (Canadian journal of cardiology, 2016)
Given changing demographics, patients with cardiovascular (CV) disease in developed countries are now older and more complex than even a decade ago. This trend is expected to continue into the foreseeable future; accordingly, cardiologists are encountering patients with a greater number of comorbid illnesses as well as “geriatric conditions,” such as cognitive impairment and frailty, which complicate management and influence outcomes. Simultaneously, technological advances have widened the therapeutic options available for patients, including those with the most advanced CV disease. In the setting of these changes, geriatric cardiology has recently emerged as a discipline that aims to adapt principles from geriatric medicine to everyday cardiology practice. Accordingly, the tasks of a “geriatric cardiologist” may include both traditional evidence-based CV management plus comprehensive geriatric assessment, medication reduction, team-based coordination of care, and explicit incorporation of patient goals into management. Given that the field is still in its relative infancy, the training pathways and structure of clinical programs in geriatric cardiology are still being delineated. In this review, we highlight the rationale behind geriatric cardiology as a discipline, several current approaches by geriatric cardiology programs, and future directions for the field. L’évolution démographique a fait en sorte que les patients atteints de maladie cardiovasculaire (MCV) dans les pays développés sont désormais plus âgés et présentent un état de santé plus complexe qu’il y a ne serait-ce qu’une décennie, et on s’attend à ce que cette tendance se maintienne dans un avenir prochain. Par conséquent, les cardiologues voient désormais des patients présentant un plus grand nombre de comorbidités ainsi que d’« affections gériatriques » comme des troubles cognitifs ou une grande fragilité qui compliquent la prise en charge et influent sur les issues thérapeutiques de la MCV. Dans un même temps, les avancées technologiques ont considérablement élargi les possibilités de traitement de ces patients, y compris ceux qui sont les plus lourdement atteints. C’est dans ce contexte qu’on assiste peu à peu à l’émergence d’une nouvelle spécialité médicale appelée cardiologie gériatrique, qui vise à appliquer les principes de la médecine gériatrique à la cardiologie. Ainsi, le « cardiologue gériatrique » combinera la traditionnelle prise en charge cardiovasculaire fondée sur des données probantes à une prise en charge de nature gériatrique axée sur l’évaluation du patient, la réduction du nombre de médicaments, la coordination de soins multidisciplinaires et le respect des objectifs de traitement du patient. Puisque cette spécialité en est encore à ses balbutiements, les modalités de formation et les programmes cliniques en cardiologie gériatrique sont encore en cours d’élaboration. Dans cet article, nous traitons des fondements de cette nouvelle discipline, des approches prônées par les programmes de cardiologie gériatrique actuels et des possibles orientations futures de cette discipline.